2018
DOI: 10.1177/0040517518767155
|View full text |Cite
|
Sign up to set email alerts
|

Ionic shot noise in an electrochemical capacitor system made of poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonate) film and silver-coated polybenzoxazole-stainless steel electrodes on textile fabrics

Abstract: Unusual noisy discharge profiles were observed from some of our textile-based energy storage devices having asymmetrical electrodes consisting of pure stainless steel and silver-coated polybenzoxazole yarns. Our hypothesis was that it was due to the ionic shot noise behavior that occurred in electrochemical devices and is a well-known phenomenon in electronic devices. The poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonate) (PEDOT:PSS) polymer coverage on the cell surface, which functioned as a solid electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…However, this was not the focus of this study, so we do not present any data or analysis regarding the distribution and molecular or electronic interaction of PEDOT:PSS in the cell area. As shown in Figure 2 , as a result of water repellent-pretreatment, PEDOT:PSS coating became concentrated within the cell area whereas in the devices reported previously [ 20 , 33 , 34 , 35 , 36 ], the polymer migrated out of the cell area. It demonstrated that the technique could be used to control the loading and distribution of PEDOT:PSS polymer dispersion during the coating process.…”
Section: Resultsmentioning
confidence: 75%
See 3 more Smart Citations
“…However, this was not the focus of this study, so we do not present any data or analysis regarding the distribution and molecular or electronic interaction of PEDOT:PSS in the cell area. As shown in Figure 2 , as a result of water repellent-pretreatment, PEDOT:PSS coating became concentrated within the cell area whereas in the devices reported previously [ 20 , 33 , 34 , 35 , 36 ], the polymer migrated out of the cell area. It demonstrated that the technique could be used to control the loading and distribution of PEDOT:PSS polymer dispersion during the coating process.…”
Section: Resultsmentioning
confidence: 75%
“…As the curves still show the typical charge-discharge profile of our device, the noise is neglected in our discussion. In addition, it is important to note that according to the previous publication [ 36 ], the noisy curves were observed from the devices with a thin layer of PEDOT:PSS film in the cell surface. The mobile ions inside the PEDOT:PSS gave an inevitable rise to noise.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations